2020
DOI: 10.3389/frai.2020.564878
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Detection of Flavescence Dorée Symptoms Across White Grapevine Varieties Using Deep Learning

Abstract: Flavescence dorée (FD) is a grapevine disease caused by phytoplasmas and transmitted by leafhoppers that has been spreading in European vineyards despite significant efforts to control it. In this study, we aim to develop a model for the automatic detection of FD-like symptoms (which encompass other grapevine yellows symptoms). The concept is to detect likely FD-affected grapevines so that samples can be removed for FD laboratory identification, followed by uprooting if they test positive, all to be conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Additionally, a two dimensional bud detection scheme by using a CNN for grapevines has been recently established [ 29 ]. Grapevine diseases caused by phytoplasmas have also been successfully resolved via CNNs on proximal RGB images [ 30 ], while fungal symptoms were earlier detected and successfully classified by using machine learning [ 31 ]. Ampatzidis and coworkers [ 32 ] also illustrated an innovative grapevine viral disease detection system by combining artificial intelligence and machine learning.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a two dimensional bud detection scheme by using a CNN for grapevines has been recently established [ 29 ]. Grapevine diseases caused by phytoplasmas have also been successfully resolved via CNNs on proximal RGB images [ 30 ], while fungal symptoms were earlier detected and successfully classified by using machine learning [ 31 ]. Ampatzidis and coworkers [ 32 ] also illustrated an innovative grapevine viral disease detection system by combining artificial intelligence and machine learning.…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies, using different sensors, have confirmed the potential of hyperspectral data to detect plant pathologies in a reliable manner in various pathosystems associated with grapevines, such as leafroll-associated virus-3 [22,28,29], grapevine trunk disease [30][31][32], Flavescence dorèe [33][34][35], and powdery mildew [36]. However, to date, there are no available data concerning grapevine root rot disease identification through hyperspectral images, thus making this work the pioneer.…”
Section: The Potential Of Hyperspectral Sensorsmentioning
confidence: 99%
“…This improvement is beneficial in a vineyard setting where false negatives represent infected plants that are not detected, and thus may contribute to virus spread by insect vectors to healthy plants until correctly detected and eliminated. As described by AL-Saddik et al (2017) and Boulent et al (2020), an incorrect negative prediction that keeps an infected plant in place is far more costly than a false positive prediction, leading to the removal of a healthy plant.…”
Section: Effect Of Different Parameters On Model Performances 421 Eff...mentioning
confidence: 99%